Student Creativity Through Animated Cartoon Images Using Artificial Intelligence: Does It Affect Indirect Creativity Indicators? - Aminah Zb; Wasim Khan (International Journal of Education and Teaching Zone, 2024)
This research aims to see the influence of cartoon animation media on student creativity in nutrition and food courses. This research uses quantitative descriptive methods. This research was carried out at UIN Sulthan Thaha Saifuddin Jambi, with a research population of 47 students who took nutrition and food courses in semester V. The sample in this study used a total sampling technique, namely, the entire population that was the research subject. The data collection technique uses an indirect creativity questionnaire survey on five indicators using a Likert scale with a total of 20 questions. Based on the research results, data was obtained that the use of Artificial Intelligence-based cartoon media can influence student learning creativity in nutrition and food courses with an average score of 4.46 in the good category, where in detail, each indicator, such as the Investigation Group, has an average score of 4.44 in the good category, the Pre-Knowledge Indicator with an average value of 4.13 in the Good category, then the Influence of Culture and Values ​​indicator with an average value of 4.83 in the good category, the Motivation indicator with an average value of 4.95 in the good category and the Self-Esteem indicator with an average value of 3.87 in the pretty good category. The highest creativity indicator in this research is Motivation in the good category, while the lowest in this research is the Self-Esteem creativity indicator in the quite good category.